2014
DOI: 10.2478/srj-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Winter ranging behaviour of a greater spotted eagle (Aquila clanga) in southeast Spain during four consecutive years

Abstract: Knowing the winter behaviour is essential for deciding on conservation strategies for threatened migratory species such as the greater spotted eagle (Aquila clanga). Fidelity and inter-annual variation in winter home range of an Estonian greater spotted eagle were studied during the first four years of its life by means of GPS satellite telemetry in south-eastern Spain. Results show the eagle exploited a small area (12.7 km 2 , 95% kernel) with high inter-annual fidelity during all winter stages. The A. clanga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Indeed, Greater Spotted Eagles winter in small, restricted habitat patches (Pérez-Garcia et al . 2014, Maciorowski et al . 2019), but there are no data on intraspecific competition at wintering sites; instead, several birds are recorded to share roosting and foraging sites in wintering grounds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Greater Spotted Eagles winter in small, restricted habitat patches (Pérez-Garcia et al . 2014, Maciorowski et al . 2019), but there are no data on intraspecific competition at wintering sites; instead, several birds are recorded to share roosting and foraging sites in wintering grounds.…”
Section: Discussionmentioning
confidence: 99%
“…The model built on telemetry data strongly agreed with literature data and ringing recoveries from European individuals, and therefore can be used for planning future counts of the wintering population. However, one fact has to be considered – the GSE breeding population is shifting eastwards towards the Mediterranean Basin, and telemetry studies showed GSE are mainly moving south and south-east during the autumn migration (Maciorowski et al 2014), while only single birds from Estonia and Poland were heading south-west (Pérez-García et al 2014, Maciorowski unpubl. ringing recoveries).…”
Section: Discussionmentioning
confidence: 99%
“…comm.). In scarce wintering sites in Spain this species also prefers marshes, wetlands and coastal lagoon, abundant in waders, coots and rats (Pérez-García et al 2014). Accordingly, the winter preference of the GSE towards marshes may result from two factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater spotted eagles tracked in those studies migrated south in autumn, some southwest towards Iberia, others south and south east towards Greece, the Balkan countries, Turkey and the Levant. Some birds migrated only as far as the northern rim of the Mediterranean, but others wintered in Arabia and north east and East Africa, as far south as Zambia (Meyburg et al 1998, PérezGarcía et al 2014. Tracking studies from farther east are few and of limited duration, but show birds from wintering grounds in Arabia migrating toward summering areas in northern Kazakhstan, and bordering areas of Russia in eastern Europe and western Siberia (Meyburg et al 1995, Strick et al 2011.…”
Section: Introductionmentioning
confidence: 99%